2005
DOI: 10.1044/1058-0360(2005/007)
|View full text |Cite
|
Sign up to set email alerts
|

Story Presentation Effects on Children’s Retell Content

Abstract: This study investigated the possibility that the amount of content children include in their stories is affected by how stories are presented. Simple stories were presented to kindergarten and Grade 2 children in 3 conditions: orally (oral only), pictorially (pictures only), and combined oral and pictures. The kindergarteners recalled more content in the combined condition than in pictures, only. The 2nd graders recalled more content in the oral only and combined conditions than in pictures only. The grades di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 20 publications
5
48
1
4
Order By: Relevance
“…Το εύρημα αυτό έρχεται σε συμφωνία με πα-λαιότερα ερευνητικά δεδομένα που υποστηρίζουν πως τα παιδιά έχουν καλύτερες επιδόσεις στην αναδιήγηση από ό,τι στην παραγωγή της αφήγησης (Boudreau, 2008). Στην ελεύθερη αφήγηση το παιδί δεν έχει στη διάθεσή του κάποια ιστορία-πρότυπο, όπως στην αναδιήγη-ση, γι' αυτό είναι δυσκολότερο να εξάγει πληροφορίες αναφορικά με τη δομή και το περιε-χόμενο μιας ιστορίας (Schneider & Dubé, 2005).…”
Section: τα αφηγηματικά επίπεδα κατά την προσχολική και πρώτη σχολικήunclassified
“…Το εύρημα αυτό έρχεται σε συμφωνία με πα-λαιότερα ερευνητικά δεδομένα που υποστηρίζουν πως τα παιδιά έχουν καλύτερες επιδόσεις στην αναδιήγηση από ό,τι στην παραγωγή της αφήγησης (Boudreau, 2008). Στην ελεύθερη αφήγηση το παιδί δεν έχει στη διάθεσή του κάποια ιστορία-πρότυπο, όπως στην αναδιήγη-ση, γι' αυτό είναι δυσκολότερο να εξάγει πληροφορίες αναφορικά με τη δομή και το περιε-χόμενο μιας ιστορίας (Schneider & Dubé, 2005).…”
Section: τα αφηγηματικά επίπεδα κατά την προσχολική και πρώτη σχολικήunclassified
“…Schneider and Dubé (1997) found that normally developing preschool children used references more adequately in response to an audio-only presentation than when formulating stories themselves from pictures only. Schneider and Dubé (2005) used the same three elicitation modalities as they had previously used (1997) in similar study populations, but investigated the impact of the presentation modalities on story grammar units produced by the children. Their results indicated that all children performed similarly during the visual-only modality, and that this modality elicited the least story grammar units for both age groups.…”
Section: Visual and Auditory Input Modalities In Narrative Assessmentmentioning
confidence: 99%
“…The first is that pictures often result in simple naming of items rather than more complex expressive language. For example, young children below the age of 5 tend to rely on picture description rather than story narration (Schneider, 1996;Schneider & Dubé, 2005). In McCabe et.…”
Section: Choice Of Materialsmentioning
confidence: 99%